Large loop-coupling enhancement of a heavy pseudoscalar from a light dark sector - Stefano Di Chiara; Andi Hektor; Kristjan Kannike; Luca Marzola; Martti Raidal (Nuclear Physics B, 2017)
The small background and the sensitivity to charged particles via a leading order loop coupling make the diphoton channel a privileged experimental test for new physics models. We propose a simple archetypal scenario to generate a sharp di-photon resonance as a result of threshold enhancements in the effective coupling between a heavy pseudoscalar particle and new vector-like leptons. We therefore study three different scenarios consistent with the current experimental limits and deviating from the Standard Model at the 2 σ level. The model also introduces a natural dark matter candidate able to match the observed dark matter abundance and comfortably respect the current direct detection constraints.